Android-Based Statistics Adventure Educational Games to Enhance Students’ Understanding of Measures of Central Tendency and ICT Literacy - Fatahillah, Arif; Ningsih, Mirah Wahyu; Monalisa, Lioni Anka; Kristiana, Arika Indah; Hussen, Saddam (Jurnal Pendidikan Matematika, 2025)
In the era of society 5.0, one of the essential skills students must possess is ICT literacy. This skill can be developed through the use of technology-integrated learning media. One of the technology-based learning media that can be used is educational games. This study aims to examine the effectiveness of the Statistics Adventure educational game in enhancing students' understanding of measures of central tendency and ICT literacy. The ICT literacy components assessed include access, manage, integrate, evaluate, and create. This research specifically focuses on the "create" component. Data were collected using questionnaires, interviews, and tests. The participants were 28 seventh-grade students from SMP Negeri 3 Jember. The results show that the Statistics Adventure game is effective in enhancing students' ICT literacy, with an overall N-Gain score of 0.8, categorized as high. The N-Gain values for each indicator are as follows: access (0.84), manage (0.87), integrate (0.84), evaluate (0.72), and create (0.92), with "create" showing the highest gain. Furthermore, the game is also effective in enhancing students’ understanding of the subject matter, with an N-Gain score of 0.5. These findings suggest that educational games can significantly enhance both ICT literacy and content comprehension among students. Kemampuan yang perlu dimiliki siswa pada era society 5.0 saat ini adalah kemampuan literasi ICT. Kemampuan literasi ICT dapat dicapai melalui penggunaan media pembelajaran yang memanfaatkan teknologi. Salah satu media pembelajaran berbasis teknologi yang dapat digunakan adalah game edukasi. Penelitian ini bertujuan untuk menguji efektifitas penggunaan game edukasi Statistics Adventure untuk meningkatkan pemahaman siswa tentang materi pemusatan data statistika dan literasi TIK. Aspek ICT meliputi Access, Manage, Integrate, Evaluate, dan Create. Pada penelitian ini aspek yang akan diteliti adalah aspek create. Model pengembangan yang digunakan adalah ADDIE terdiri dari lima tahap yaitu Analyze (Analisis), Design (Desain), Development (Pengembangan), Implementation (Implementasi), dan Evaluate (Evaluasi). Metode pengumpulan data yang digunakan adalah angket, wawancara, dan tes. Subjek penelitian ini adalah siswa kelas VII SMP Negeri 3 Jember sebanyak 28 siswa. Keefektifan game edukasi Statistics Adventure efektif untuk meningkatkan ICT Literacy siswa dengan nilai N-Gain yang diperoleh sebesar 0,8 sehingga efektif dengan kategori tinggi. Nilai N-gain setiap indikator menunjukkan peningkatan, Access (0,84), Manage (0,87), Integrate (0,84), Evaluate (0,72), dan Create (0,92). Aspek Create merupakan aspek dengan nilai N-Gain tertinggi. Berdasarkan hal tersebut dapat disimpulkan bahwa game edukasi dapat meningkatkan ICT literacy siswa dengan kategori tinggi. Game edukasi ini juga efektif untuk meningkatkan pemahaman siswa dengan nilai N-Gain sebesar 0,5.